1H NMR metabolomic and transcriptomic analyses reveal urinary metabolites as biomarker candidates in response to protein undernutrition in adult rats. Issue 6 (28th March 2021) - Komatsu, Yosuke; Wada, Yasuaki; Izumi, Hirohisa; Shimizu, Takashi; Takeda, Yasuhiro; Aizawa, Tomoyasu
Abstract: Protein undernutrition contributes to the development of various diseases in broad generations. Urinary metabolites may serve as non-invasive biomarkers of protein undernutrition; however, this requires further investigation. We aimed to identify novel urinary metabolites as biomarker candidates responsive to protein undernutrition. Adult rats were fed control (CT; 14 % casein) or isoenergetic low-protein (LP; 5 % casein) diets for 4 weeks. 1 H NMR metabolomics was applied to urine, plasma and liver samples to identify metabolites responsive to protein undernutrition. Liver samples were subjected to mRNA microarray and quantitative PCR analyses to elucidate the mechanisms causing fluctuations in identified metabolites. Urinary taurine levels were significantly lower in the LP group than in the CT group at week 1 and remained constant until week 4. Hepatic taurine level and gene expression level of cysteine dioxygenase type 1 were also significantly lower in the LP group than in the CT group. Urinary trimethylamine N-oxide (TMAO) levels were significantly higher in the LP group than in the CT group at week 2 and remained constant until week 4. Hepatic TMAO level and gene expression levels of flavin-containing mono-oxygenase 1 and 5 were also significantly higher in the LP group than in the CT group. In conclusion, urinary taurine and TMAO levels substantially responded to protein undernutrition. Furthermore, changes in hepatic levels of these metabolites and gene expressions associated with their metabolic pathways were also reflected in their fluctuating urinary levels. Thus, taurine and TMAO could act as non-invasive urinary biomarker candidates to detect protein undernutrition. Abstract :